Cavernous carotid aneurysms: a new treatment paradigm in the era of flow diversion. (1st February 2017) - Raper, Daniel M. S.; Ding, Dale; Peterson, Eric C.; Crowley, Richard W.; Liu, Kenneth C.; Chalouhi, Nohra; Hasan, David M.; Dumont, Aaron S.; Jabbour, Pascal; Starke, Robert M.
ABSTRACT: Introduction : Cavernous carotid aneurysms can cause significant symptomatology through mass effect and may rupture, resulting in carotid-cavernous fistula or epistaxis. Traditional treatment options included endovascular or surgical parent vessel occlusion, or embolization; in the last decade, the development of flow-diverting stents has changed the management paradigm for these lesions. Areas c overed : In this review, we summarize the natural history, clinical presentation, and evolution of treatment options for cavernous carotid aneurysms and discuss developments likely to influence treatment strategies in the future. We performed a Medline search for relevant review articles and original reports and additional searches based on review of referenced articles, abstracts, and conference presentations. Expert c ommentary : Long-term data are still required to fully assess the efficacy of endoluminal reconstruction using flow diversion, but this approach appears to offer an attractive therapy for many cavernous carotid aneurysms requiring intervention.